Danish naval officers in foreign service: knowledge transfer in mid-eighteenth-century Europe. (2nd January 2021) - Jorgensen, Ida Christine
ABSTRACT: In 1756, two Danish naval officers went into French service. This was a common practice in eighteenth-century Denmark, which aimed to train the officers and to gather intelligence on naval construction as well as navigation, administration, and victualling. Detailed descriptions of French warships can be found in the reports from the two officers, which are kept in the Danish National Archives in Copenhagen. Together with the protocols from the Construction Committee, responsible for shipbuilding, it is evident that aspects of ship designs were transferred from the French to the Danish navy.